2012
DOI: 10.1007/s00270-012-0496-8
|View full text |Cite
|
Sign up to set email alerts
|

Does Mechanical Thrombectomy in Acute Embolic Stroke Have Long-term Side Effects on Intracranial Vessels? An Angiographic Follow-up Study

Abstract: De novo stenoses and occlusions occur in a small proportion of patients after mTE. Because all lesions were clinically asymptomatic, this finding does not affect the overall benefit of the treatment. Vasospasm may predict late vessel wall changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 23 publications
2
50
2
Order By: Relevance
“…Previous research has shown that the extent and depth of the vascular lesion may be contributing factors in promoting early atherosclerotic and accelerated hyperplastic intimal and medial changes. 26 Large areas of endothelial denudation without substantial medial trauma caused only mild intimal thickening, whereas focal endothelial denudation with substantial medial trauma produces marked delayed intimal thickening. 27 These results are substantiated by those of other studies that have shown that smooth muscle cells are normally quiescent with respect to proliferation but that deep injuries result in the expression of a phenotype of vascular smooth-muscle cells that exhibits a high proliferative response to other mitogens.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that the extent and depth of the vascular lesion may be contributing factors in promoting early atherosclerotic and accelerated hyperplastic intimal and medial changes. 26 Large areas of endothelial denudation without substantial medial trauma caused only mild intimal thickening, whereas focal endothelial denudation with substantial medial trauma produces marked delayed intimal thickening. 27 These results are substantiated by those of other studies that have shown that smooth muscle cells are normally quiescent with respect to proliferation but that deep injuries result in the expression of a phenotype of vascular smooth-muscle cells that exhibits a high proliferative response to other mitogens.…”
Section: Discussionmentioning
confidence: 99%
“…Its incidence is reportedly 20%-26%. 1,2) Furthermore, patients with restenosis in the chronic phase after mechanical thrombectomy have also been reported. 1,3) However, to our knowledge, there is no case report of symptomatic cerebral vasospasm occurring a few days after surgery and an improvement achieved by medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral vasospasm is relatively frequent as a complication related to mechanical thrombectomy, 1,2) but is temporarily observed during surgery to immediately after surgery in most cases. No study has reported delayed cerebral vasospasm.…”
Section: Introductionmentioning
confidence: 99%
“…Although stent retrievers have been shown to be safe and effective, 10) the possibility of latent risk of stenosis or occlusion of the treatment site associated with the deployment and traction of the stent retriever has begun to be recognized. 8,11) These events are considered to be caused primarily by endothelial injury. There have been a few histological studies to evaluate the effects of percutaneous intracranial thrombectomy on the treated blood vessel by animal experiments, and Teng et al 12) and Arai et al 13) demonstrated endothelial injury after the use of stent retrievers by animal experiments in the porcine femoral artery and rabbit carotid artery.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] However, there is a risk of stenosis or occlusion in the chronic phase, and the possibility of an involvement of intimal injury has recently been suggested. 8) We report a case that showed exacerbation of a stenotic lesion in the chronic phase after treatment of cerebral infarction due to basilar artery occlusion using a stent retriever.…”
Section: Introductionmentioning
confidence: 99%